Photocatalytic glucose depletion and hydrogen generation for diabetic wound healing - Shengqiang Chen; Yanxia Zhu; Qingqing Xu; Qi Jiang; Danyang Chen; Ting Chen; Xishen Xu; Zhaokui Jin; Qianjun He (Nature Communications, 2022)
Hydrogenation is a treatment for chronic inflammation caused by high glucose levels in diabetic ulcers, However, current therapies have limitations. Here, the authors report on the creation of a visible light photocatalytic agent which depletes glucose in the wound and generates hydrogen to aid in diabetic wound healing.